BIOMASSA TUMBUHAN BAWAH PADA BERBAGAI TIPE HUTAN ALAM DI NEGERI HATUSUA. PROVINSI MALUKU. - Moh Firdaus Rahawarin; Irwanto Irwanto; Miranda Hadijah (MARSEGU : Jurnal Sains dan Teknologi, 2025)
Understory biomass plays an important role in maintaining forest ecosystem balance and the carbon cycle. This study aims to measure and compare understory biomass across various natural forest types in Hatusua Village, Maluku, namely Coastal Forest, Mangrove Forest, Dominant Aren Forest, and Lowland Forest. The method used includes systematic sampling with 2x2 meter plots, considering dense, moderate, and sparse conditions, where all understory plants were collected, weighed, and dried to estimate dry biomass. The results showed that the highest biomass was found in the Coastal Forest (2,716.14 kg/ha), followed by the Mangrove Forest (2,545.87 kg/ha), the Lowland Forest (1,841.72 kg/ha), and the lowest in the Dominant Aren Forest (1,629.33 kg/ha). This biomass variation is influenced by light intensity, soil conditions, and vegetation structure. Carbon content calculations based on biomass indicate that the Coastal Forest has the highest carbon storage, followed by the Mangrove Forest, Lowland Forest, and Dominant Aren Forest. This study confirms that understory biomass is a vital component of forest ecosystems, requiring attention in conservation efforts and climate change mitigation.